علم مقارنة الأديان وأثره في تعميق فهم القرآن الكريم - شتيوي سفيان (University of Eloued جامعة الوادي, 2024)
يعد علم مقارنة الأديان من العلوم التي ظهرت في البيئة الإسلامية بدافع من القرآن الكريم ابتداءا، من خلال إشاراته العديدة إلى الأديان والشرائع والكتب المقدسة عرضا ونقدا ومقارنة، وهي الإشارات التي كانت منطلق ومستند علماء المسلمين في دراستهم للأديان المختلفة. وهذه الدراسة محاولة جادة للوقوف على إسهامات علم مقارنة الأديان في تفسير القرآن الكريم والدراسات القرآنية عموما، وتدور الإشكالية حول طبيعة الإضافات التي يمكن أن يقدّمها علم مقارنة الأديان لعلم التفسير والدراسات القرآنية. ومن النتائج التي توصلت إليها أن لعلم مقارنة الأديان إسهامات لا يمكن إغفالها في الدرس التفسيري تدور حول تعميق فهم النص وتوسيع فهمه، والتأكيد على صدق وصحة الإشارات القرآنية في المباحث المتعلقة بالأديان، من خلال خلاصة أبحاثه والنتائج التي توصل إليها علماؤه. Abstract : The science of comparative religions is one of the sciences that emerged in the Islamic environment, motivated by the Holy Qur’an, starting with, through its many references to religions, laws and holy books in presentation, criticism and comparison, and these are the signals that were the starting point and basis for Muslim scholars in their study of different religions. This study aims to demonstrate the contributions of the science of comparative religions in the interpretation of the Holy Qur’an and Quranic studies in general. One of my findings is that the science of comparative religions has contributions that cannot be overlooked in the exegetical lesson that revolve around deepening understanding of the text and expanding its understanding, and emphasizing the sincerity and validity of the Qur’anic references in the investigations related to religions, through the summary of its research and the findings of its scholars.
Keywords: مقارنة الأديان; القرآن الكريم; الإطار المرجعي; الإسهامات